PEMAKNAAN PENGALAMAN BUDAYA UTANG PADA UPACARA KEMATIAN RAMBU SOLO’ BAGI MASYARAKAT TORAJA YANG MERANTAU - Padang, Emastya Lisu; Doddy Hendro Wibowo (Bajang Institute, 2024)
Rambu Solo' culture is a culture that has been adopted as a belief of the Toraja people. The Torajan people's understanding of the rituals at the Rambu Solo' ceremony causes families to try to carry out the Rambu Solo' ceremony by looking for large costs and being able to borrow from various sources in order to carry out the ceremony in a grand manner. This research aims to determine attitudes towards the culture of debt at the Rambu Solo' death ceremony for Torajan people who have migrated. This type of research is descriptive qualitative research. Data collection used included in-depth interview techniques. This research involved three Torajan participants who migrated and implemented a debt culture. The data organization and analysis technique that will be used is the analytical descriptive method. The results of this research show that attitudes towards debt culture at the Rambu Solo' death ceremony for Toraja people who migrate do have an impact after they leave Toraja to migrate. It can be seen from the change in thinking about debt itself, which according to them is not a good thing to do, so there is a shift in meaning in the culture of Rambu Solo'.